Enhancing health quality of Prolanis Participants through telepharmacy, interactive education, and medication management tools - Sukmawati Sukmawati; Andi Maulana Kamri; Sitti Nurana; Namira Madi; Nurul Nur Insyirah; Maulidi Sahrani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
This community service activity was carried out in response to the challenges of managing chronic diseases faced by Prolanis participants at the Jumpandang Baru Public Health Centre in Makassar. This program employs a multidimensional strategy encompassing interactive health education, telepharmacy technology via WhatsApp, the provision of pill cards for medication management, and system enhancement through collaboration with health personnel and local government. The evaluation was conducted by pre-tests and post-tests on 24 initial respondents, with the results demonstrating a considerable increase in comprehending medication adherence (average score 14.05 to 14.54) and monitoring treatment effectiveness (13.84 to 14.29). Simultaneously, comprehension of the Patient Companion's (PMO) role remained continuously elevated (24.47 to 24.54), signifying a robust knowledge foundation in this domain. The participation rate rose to 24 responses in the post-test, signifying favourable community interest and acceptability. The expected outcomes of this activity in the near future are an increase in patient independence, patient-volunteer relationships, or the telepharmacy workflow of the community health centre. Notwithstanding the limitations imposed by inadequate health facility facilities, this program effectively enhanced participants' health knowledge and conduct. The program's sustainability is advised through regular mentoring, official incorporation of telepharmacy services, and optimisation of local resources.